HUBUNGAN ANTARA DUKUNGAN KELUARGA DAN MOTIVASI MELAKUKAN ROM PADA PASIEN PASCA STROKE - siti nuryanti (MNJ (Mahakam Nursing Journal), 2016)
The role of the family is needed for post-stroke care for family members who generally suffer sequelae that impact on reliance in meeting basic needs. Family support will motivate family members with post-stroke rehabilitation thus helping the recovery process. The purpose of this study was to determine the relationship between Family Support and Motivation Doing Range Of Motion (ROM) on Post-Stroke Patients in Hospital Dr. Kanudjoso Balikpapan. This type of research is descriptive analytic and cross sectional study design. This research was conducted in Poli Poli Neuroscience and Medical Rehabilitation Hospital Dr. Kanudjoso. Sampling was done by purposive sampling with the number of 60 samples. The results showed no association with the motivation of support information p value = 0,000, there is a relationship of emotional support and motivation p value = 0.005, no instrumental support relationships with the motivation p value = 0,002, there is a relationship of support with motivational awards p value = 0,000, whereas the most dominant factor related to patient motivation did ROM is variable information support wald p (pvalue = 0,003). The hospital suggested to improve information support families in post-stroke patients, for caregivers improve nursing care in patients with post-stroke, for the development of science to follow-up studies using other variables and different research methods that can be used as a comparison.